Ответы и объяснения

2014-03-27T20:42:55+04:00
А. -3х+5х=2,4
2х=2,4
Х=1,2

Б. 2(у+1)+5(у-0,4)=14
2у+2+5у-2=14
7у=14
У=2

С. -8х+2х+3х=-12
-3х=-12
Х=4

Д. 5х-(2х-9)=6+(Х+3)
5х-2х+9=6+Х+3
3х-Х=-9+9
2х=0
Х=0

Е. 7х-8=4х-(1-3х)
7х-8=4х-1+3х
7х-4х-3х=8-1
0х=7
Х=0

Ф. 4х^2-25=0
4х^2=25
Х^2=6,25
Х=+-2,5

(Х+4)^2-(Х-3)^2=35
Х^2+8х+16-(х^2-6х+9)=35
Х^2+8х+16-х^2-6х-9=35
2х=28
Х=14

Х^2-7х+6=0
D=49-24=25
X1=(7+5)/2=6
X2=(7-5)/2=1

X^2-15x+50=0
D=225-200=25
X1=(15+5)/2=10
X2=(15-5)/2=5

169-x^2=0
X^2=169
X=+-13

2x^2+x=0
X(2x+1)=0
X1=0
2x+1=0
2x=-1
X=-0,5

X^2-6x-16=0
D=36+64=100
Х1=(6+10)/2=8
Х2=(6-10)/2=-2

3х^2-Х-4=0
D=1+48=49
X1=(1+7)/2=4
X2=(1-7)/2=-3

2x^2+5x+2=0
D=25-16=9
X1=(-5+3)/4=-0,5
X2=(-5-3)/4=-2